Enhanced catalytic activity through a unique cage structure of amorphous NiFe oxide via tri-doping P, B, N and introducing tungsten for the oxygen evolution reaction - Jang, Eunsu (2024)
Unique designs and doping strategies were adopted to control the variability of intrinsic active sites and to enhance the catalytic performance of bimetal catalysts in the oxygen evolution reaction (OER). This study introduces the fabrication of unique cage-structured NiFe-W-PBN oxide catalysts (u-NFWPBNO) through a facile stepwise reduction process. The two-step metal reduction, employing H4N2·H2O followed by NaBH4, yields a cage structure (120 nm) featuring an uneven shell surface composed of small nanospheres (25 nm). Outstanding OER performance is achieved, which can be attributed to the P, B, N tri-doping strategy including both geometric and electronic structural changes. Furthermore, the introduction of tungsten (W) results in electron withdrawal at the metal centers. P, B and P, N dual-doped catalysts with different morphologies (NFWPBO, NFWPNO) and W-free (NFPBNO) comparison groups were prepared to compare these features. Consequently, u-NFWPBNO exhibits overpotentials of 256 mV for j10 and a Tafel slope of 32 mV/dec, demonstrating high performance. This study serves as a valuable guide for preparing uniquely designed, high-activity amorphous electrocatalysts and provides insights for developing Zn-air batteries.